Different Kinds of 3T2R Serial Kinematic Chains and Their Applications in Synthesis of Parallel Mechanisms. (February 2020) - Yang, Shuofei; Li, Yangmin
Highlights: New-kind 3 T 2 R motion with one fixed and one variable rotation directions is defined. 3 T 2 R motions are classified based on the relationships between rotations in a motion. The serial kinematic chains generating the new motions are analytically synthesized. The obtained serial kinematic chains are applied in synthesis of parallel mechanisms. Abstract: This paper proposes a new-kind three-translational and two-rotational (3 T 2 R ) motion with one fixed and one variable rotation directions. The serial kinematic chains (SKCs) that generate the proposed motions are synthesized. They are quite different from the SKCs generating 3 T 2 R motion with two fixed rotation directions. Firstly, according to the relationships between the two rotations in a motion, the classification of 3 T 2 R motions is discussed. By using finite screw as mathematical tool, the expressions of the two different kinds of 3 T 2 R motions are formulated as algebraic sets. Secondly, serial motion generators of the 3 T 2 R motions are investigated. The SKCs that generate the first-kind 3 T 2 R motion are briefly reviewed; the twenty-eight types of SKCs that generate the second-kind 3 T 2 R motion are synthesized by analytical derivations. Finally, the SKCs with the second-kind 3 T 2 R motion are used to synthesize new parallel mechanisms. Two five-degree-of-freedom (five-DoF) systematical parallel mechanisms are taken as examples to show the applications of these SKCs. This paper provides theoretical foundations for the research on motions generated by complex SKCs and on motion patterns with variable rotation directions and centers.